Ferroptosis induces nucleolar stress as revealed by live-cell imaging using thioflavin T - Yoko Hirata; Hiroshi Takemori; Kyoji Furuta; Yuji O. Kamatari; Makoto Sawada (Elsevier, 2024)
Nucleolar stress induced by stressors like hypoxia, UV irradiation, and heat shock downregulates ribosomal RNA transcription, thereby impairing protein synthesis capacity and potentially contributing to cell senescence and various human diseases such as neurodegenerative disorders and cancer. Live-cell imaging of the nucleolus may be a feasible strategy for investigating nucleolar stress, but currently available nucleolar stains are limited for this application. In this study using mouse hippocampal HT22 cells, we demonstrate that thioflavin T (ThT), a benzothiazole dye that binds RNA with high affinity, is useful for nucleolar imaging in cells where RNAs predominate over protein aggregates. Nucleoli were stained with high intensity simply by adding ThT to the cell culture medium, making it suitable for use even in damaged cells. Further, ThT staining overlapped with specific nucleolar stains in both live and fixed cells, but did not overlap with markers for mitochondria, lysosomes, endoplasmic reticulum, and double-stranded DNA. Ferroptosis, an iron-dependent nonapoptotic cell death pathway characterized by lipid peroxide accumulation, reduced the number of ThT-positive puncta while endoplasmic reticulum stress did not. These findings suggest that ferroptosis is associated with oxidative damage to nucleolar RNA molecules and ensuing loss of nucleolar function.